Pengembangan Website Perpustakaan untuk Mendukung Layanan Digital - Mukhotib; Mustar, Maniso (Perpustakaan Universitas Gadjah Mada, 2023)
The rapid technological advancements and the evolving needs of users, as well as the requirements of the parent institution, demand libraries to engage in development and innovation according to user preferences. One of the developments and innovations undertaken by libraries is the establishment of collections and services in digital formats. The Faculty of Medicine, Public Health, and Nursing Library at Gadjah Mada University has built a digital collection and service by developing a website at the link http://infolib.med.ugm. The purpose of this article is to explain best practices employed by the library in developing the library website to support digital services. The website at htttp://infolib.med.ugm contains digital content as one solution to optimize services and meet the needs of academic communities and institutional bodies. The development of this website was initiated in 2005. The website is crucial for the academic community to support learning, research, and access accurate information. However, the website faced challenges and became inaccessible, leading to the creation of Website htttp://infolib.med.ugm release 2 in 2021. There are fundamental differences from the previous release in 2005. In Release 2, the available collection consists solely of digital materials, including books, scholarly works, journal articles, proceedings, and videos. This website proves highly valuable and beneficial in addressing the needs of users to support education, research, and community service.